“El ladrón de cerebros” de Pere Estupinyá - Ortega San Martín, Luis (2013)
Review of some of the most important and interesting passages of the popular science book “El ladrón de cerebros” written by Pere Estupinyá. Debolsillo: Barcelona, 2010. 450 pages. ISBN: 978-84-9989-384-6